Treatment of patients with severe aplastic anaemia with allogeneic stem cell transplantation - single centre experience - Popova-Labachevska, Marija; Pivkova Veljanovska, Aleksandra; Trajkova, Sanja; Chadievski, Lazar; Georgievski, Borche; Chevrevska, Lidija; Ridova, Nevenka; Stojanovska Jakimovska, Simona; Grivchevska, Milena; Labachevski, Bojan; Panovska Stavridis, Irina (Macedonian Pharmaceutical Association, Ss. Cyril and Methodius University in Skopje, Faculty of Pharmacy, 2022)
Aplastic anemia is a rare hematological syndrome caused by bone marrow failure and pancytopenia. It can be either inherited or acquired, the second one being more common. A variety of trigger factors have been implicated in the etiology of acquired aplastic anemia. However, in around 70% of the cases, the reason remains unknown. The two first line treatment options with competitive rate of success are immunosuppressive therapy (IST) and allogeneic stem cell transplantation (SCT). In this retrospective study we present our experience in the treatment of thirteen patients with severe acquired aplastic anemia. Six of the patients mentioned underwent matched unrelated (MUD) SCT and had all been previously treated with IST, except for one patient. The remaining seven patients included in our study underwent matched related SCT, without previous IST. Conditioning regimen, graft versus host prophylaxis, veno occlusive disease prophylaxis, antimicrobial prophylaxis and treatment, source of stem cells, as well as blood counts were taken into account, within a 7 year follow up period on average. Our findings revealed an overall survival rate of 92%. Three cases of graft versus host disease were observed, two within the MUD SCT group of patients (33%) and one within the matched related SCT group (17%). Faster engraftment was reached in patients treated with matched related SCT. One patient demanded a second allogeneic SCT. Comparable to other findings in literature, our study corroborated the favorable outcome of both allogeneic related and unrelated hematopoietic stem cell transplantation in the treatment of patients with severe aplastic anemia.
Keywords: aplastic anemia; stem cell transplantation; immunosupressive therapy